Recent Translations of the Medieval Icelandic Bishops' Sagas - Patzuk-Russell, Ryder C. (Scandinavian-Canadian Studies / Études scandinaves au Canada)

(untitled) (Association for the Advancement of Scandinavian Studies in Canada, 2023)
This article reviews two recent English-language translations of medieval Icelandic bishops’ sagas, and contextualizes them in the history of translations from this genre. Margaret Cormack’s The Saga of St. Jón of Hólar and Theodore M. Andersson’s Bishops in Early Iceland were both published in 2021, and make important contributions to the growing interest in medieval Icelandic ecclesiastical history and religious literature. Cormack’s book provides a more precise translation and is accompanied by a thorough study of the saga and its themes, while Andersson provides a more accessible and approachable if somewhat more limited work. These publications are part of body of new translations in the genre, which has flourish since 2000, after a long period of neglect.